2022
DOI: 10.3390/plants11091250
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Triterpene Saponin Glycyrrhizin Transport by Glycyrrhiza glabra

Abstract: Glycyrrhizin (GL), a triterpene compound produced by Glycyrrhiza species, is a crucial pharmacologically active component of crude drugs. In contrast to the biosynthesis of GL in plants, little is known about GL transport and accumulation in plants. The transport mechanism of GL was characterized using cultured cells of Glycyrrhiza glabra. Cultured cells of G. glabra efficiently incorporated exogenously supplied GL. Proton pump inhibitors, such as probenecid and niflumic acid, as well as a protonophore (carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…With the synthesis of large molecules that come from heterologous species, transporters and accessory proteins may become increasingly important for the glycosylation of these natural products. The plant vacuole is often used to store secondary metabolites like saponins, and ABC-type transporters are likely used to allow these metabolites to enter the vacuole. , For example, avenacin A1 is a saponin found in Avena strigosa, where the last two biosynthetic steps occur in the vacuole, including the final glycosylation step, and this molecule could be synthesized in N. benthamiana without the addition of any transporters. , These transporters are largely uncharacterized, though it is likely that many plants share this machinery.…”
Section: Discussionmentioning
confidence: 99%
“…With the synthesis of large molecules that come from heterologous species, transporters and accessory proteins may become increasingly important for the glycosylation of these natural products. The plant vacuole is often used to store secondary metabolites like saponins, and ABC-type transporters are likely used to allow these metabolites to enter the vacuole. , For example, avenacin A1 is a saponin found in Avena strigosa, where the last two biosynthetic steps occur in the vacuole, including the final glycosylation step, and this molecule could be synthesized in N. benthamiana without the addition of any transporters. , These transporters are largely uncharacterized, though it is likely that many plants share this machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent study reported the identification of four members of plasma membrane-localized ABCG transporters in Salvia miltiorrhiza Bunge, a plant used in traditional Chinese medicine to treat cardiovascular and cerebrovascular diseases; these transporters could be potentially involved in the export of tanshinone (a lipophilic diterpene) and salvianolic acid (a hydrophilic phenolic compound), which are metabolites highly accumulated in the roots and rhizomes of S. miltiorrhiza [ 129 ]. Additionally, in the present Special Issue, Kato and coauthors described the transport of the triterpene saponin glycyrrhizin in Glycyrrhiza glabra (licorice plant) by a H + -symporter in the plasma membrane and by an ATP-binding cassette transporter in the vacuole (with a high specificity for the aglycone form) [ 130 ].…”
Section: Function and Transport Of Terpenesmentioning
confidence: 99%